Pengaruh Budaya Organisasi terhadap Kinerja Karyawan: Peran Mediasi Manajemen Perubahan pada PT. Prambanan Dwipaka - I Nyoman Trisatya Rhenanda; Dewi Nuraini (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2026)
PT. Prambanan Dwipaka faces a restructuring challenge through a transition from a manual to a fingerprint attendance system, which has triggered cultural and operational resistance. This associative quantitative study aims to analyze the effect of organizational culture on employee performance, using change management as a mediating variable. The sample was determined using a purposive sampling method, comprising 168 permanent employees. Data collection was conducted through structured questionnaires via Google Forms, while data analysis utilized Structural Equation Modelling based on Partial Least Squares (SEM-PLS) via SmartPLS 4. The results indicate that organizational culture has a positive & significant effect on employee performance (coefficient= 0.484; p value= 0.000) and on change management (coefficient= 0.697; p value= 0.000). Furthermore, change management is proven to have a positive and significant effect on employee performance (coefficient= 0.335; p value= 0.003). The indirect effect test confirms that change management significantly mediates the relationship between organizational culture and employee performance, exhibiting partial mediation (koefisien= 0.233; p value= 0.004). Academically, this finding proves that an adaptive organizational culture requires tactical change management as an operational mediator to optimize work productivity. Practically, the company is advised to align cultural values with structured transition management to minimize job anxiety and maintain stable field performance.